Implementasi Pembelajaran Biologi Berbasis Gambar Interaktif Untuk Meningkatkan Berpikir Kritis Peserta Didik Materi PencemaranLingkungan - Nunuk Rodiyah (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2023)
This research is motivated by the non-optimal achievement of students' critical thinking skills. This non-optimal learning result is caused by the learning process which is still teacher-centered, the lack of use of learning media, and the lack of involvement of students' experiences in constructing their knowledge. To overcome this through classroom action research, researchers utilize learning media in the form of interactive images carried out in learning with the discovery learning model with the hope of increasing student learning outcomes. This research is limited to the topic of Enviromental Pollution in Class X-9 at SMA Negeri 1 Menganti. This study used a class action research method with 2 cycles. The research implementation took place in 2 (two) cycles with varying changes in learning outcomes. In the first cycle of class X-9 the learning outcomes achieved were 91.87% of the classical completeness score with an average achievement of 78.81, while in the second cycle the learning outcomes achieved in class X-9 were 100% of the classical completeness value with an average achievement 86,17. From these results it can be concluded that the use of interactive image learning media on environmental pollution material can improve students' critical thinking skills